BOOK REVIEW: Catherine Horel, “De l’exotisme à la modernité. Un siècle de voyage français en Hongrie (1818-1910)”, Montrouge, Éditions du Bourg, 2018, 225 p., ISBN: 978-2-490650-01-9 - TURCU, Lucian (Studia Universitatis Babeș-Bolyai Historia, 2018)
Catherine Horel is today a well-known name in researching the past of the Central-Eastern European space. The numerous works from this geographic area that have the French historian born in Paris in 1966 as their author or coordinator stand as testimony. Whether it is the history of the Jewish community in Hungary of the first half of the nineteenth century (analyzed at the intersection of the tendencies of identity assimilation and national emancipation) or we are referring to the history of Budapest or to the past of Central Europe in the period between the Congress of Vienna and the beginning of the third millennium or Admiral Horthy's personality or the Balkan wars of 1912-1913, all these (and others which are not mentioned here) demonstrate the variety of historical investigation sites that Catherine Horel has assumed over the years as a professor at the Panthéon-Sorbonne University in Paris and a researcher at the National Center for Scientific Research.The book we are focusing on is an updated reedition of a volume published under the same title at the Eötvös Loránd University (ELTE) in Budapest in 2004. Structurally, it consists of three chapters, preceded by an introduction and followed by conclusions, a section dedicated to the sources and bibliography used, an index of names of people, and a table that explains the 13 illustrations that can be found throughout its pages.